Evidence of topological superconductivity in planar Josephson junctions - Fornieri, Antonio; Whiticar, Alexander M.; Setiawan, F.; Marín, Elías Portolés; Drachmann, Asbjørn C. C.; Keselman, Anna; Gronin, Sergei; Thomas, Candice; Wang, Tian; Kallaher, Ray; Gardner, Geoff; Berg, Erez; et al. (Nature, 2019)
Majorana zero modes—quasiparticle states localized at the boundaries of topological superconductors—are expected to be ideal building blocks for fault-tolerant quantum computing1,2. Several observations of zero-bias conductance peaks measured by tunnelling spectroscopy above a critical magnetic field have been reported as experimental indications of Majorana zero modes in superconductor–semiconductor nanowires3–8. On the other hand, two-dimensional systems offer the alternative approach of confining Majorana channels within planar Josephson junctions, in which the phase difference φ between the superconducting leads represents an additional tuning knob that is predicted to drive the system into the topological phase at lower magnetic fields than for a system without phase bias9,10. Here we report the observation of phase-dependent zero-bias conductance peaks measured by tunnelling spectroscopy at the end of Josephson junctions realized on a heterostructure consisting of aluminium on indium arsenide. Biasing the junction to φ ≈ π reduces the critical field at which the zero-bias peak appears, with respect to φ = 0. The phase and magnetic-field dependence of the zero-energy states is consistent with a model of Majorana zero modes in finite-size Josephson junctions. As well as providing experimental evidence of phase-tuned topological superconductivity, our devices are compatible with superconducting quantum electrodynamics architectures11 and are scalable to the complex geometries needed for topological quantum computing9,12,13. Evidence is found for phase-tunable Majorana zero modes in scalable two-dimensional Josephson junctions produced by top-down fabrication.